Optimasi Pendistribusian Barang Dengan Menggunakan Vogel’s Approximation Method dan Stepping Stone Method - Yuli Ratnasari; Desi Yuniarti; Ika Purnamasari (Program Studi Statistika FMIPA Universitas Mulawarman, 2019)
The development of era and technology are getting shopisticated which impacts the increasing of company in service area. Distribution and transportation are important aspects that can affect the success of the company’s performance.Vogel’s Approximation Method the first solution to solve the transportation problem and also Stepping Stone Method for the optimum solution to get the minimum operational cost. The aim of this research is to see the difference distribution operational cost of LPG gas 3 Kg in PT. Tri Pribumi Sejati before and after applying Vogel’s Approximation Method (VAM) and Stepping Stone Method. The result shows that Vogel’s Approximation Method (VAM) spent transportation cost Rp 24.353.568,- so it saved the transportation cost for 45,9% and made difference Rp 20.646.432,-. Next, applying Stepping Stone Method optimum solution spent transportation cost Rp 24.031.104,- so it also saved the transportation cost for 46,6% and made difference Rp 20.968.896,- of total cost of PT. Tri Pribumi Sejati Rp 45.000.000,-. To sum up that using Vogel’s Approximation Method the first solution and Stepping Stone Method optimum solution are exact method to minimize the distribution operational cost of 3kg gas tube in PT. Tri Pribumi Sejati.